Study the Efficiency of Drilling With Casing Operation in an Iraqi Oil Field - Alhaleem, Ayad A. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Drilling with casing (DWC) can be considered as a modern drilling technique in which both of drilling and casing operations done in the same time by using the casing to transfer the hydraulic and mechanical power to the bit instead of traditional drilling string. To overcome oil well control, minimizing the total cost through enhancing drilling efficiency, drilling with casing was proposed as an enabling technology.   Two surface sections (17 1/2 - and 12 1/4- inch) were drilled successfully in Rumaila oil field with  casing strings which reached 655m and 1524m measured depths respectively.   By using DWC technique, the total drill/case phase time was reduced up to 20% comparing to conventional drilling in the same field .   Drilling both sections with DWC system eliminating the number of trips and nonproductive time (NPT) related to wellbore instability.